2001
DOI: 10.1046/j.1440-1746.2001.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine irrigation for the prevention of pancreatic damage after endoscopic balloon sphincteroplasty

Abstract: Epinephrine irrigation is a simple and useful method to prevent post-EBS pancreatic damage and pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Based on this theory, treatments aiming at decreasing the pressure in sphincter of Oddi have been started for reducing the post-ERCP pancreatitis risk. Recently, although nifedipine, glyceryl trinitrate (GTN), topical epinephrine or botulinum toxin have been used for this purpose, the results appear to be contradictory with each other (17)(18)(19)(20)(21)(22). GTN, the most promising one among those, is a rapid-acting short-standing nitric oxide source that considerably decreases the sphincter of Oddi pressure, which is used in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theory, treatments aiming at decreasing the pressure in sphincter of Oddi have been started for reducing the post-ERCP pancreatitis risk. Recently, although nifedipine, glyceryl trinitrate (GTN), topical epinephrine or botulinum toxin have been used for this purpose, the results appear to be contradictory with each other (17)(18)(19)(20)(21)(22). GTN, the most promising one among those, is a rapid-acting short-standing nitric oxide source that considerably decreases the sphincter of Oddi pressure, which is used in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent two meta-analyses of 10 RCTs (1554 patients and 1730 patients respectively) have concluded that allopurinol does not reduce post-ERCP pancreatitis and should be not recommended as a prophylactic agent [63,64] . Other agents studied (Adrenaline spray, pentoxifylline, platelet-activating factor acetylhidrolase, semapimod, aprepitant and risperidone) have either revealed discordant results or no effect on preventing post-ERCP pancreatitis [64][65][66][67][68][69][70][71][72][73] .…”
Section: Interruption Of Inflammatory Cascade (Anti-inflammatory): Nomentioning
confidence: 99%
“…Gabexate mesylate may reduce the incidence of especially moderate or severe pancreatitis. 41 Insertion of a pancreatic stent, 42 epinephrine irrigation after EPBD, 43 isosorbide dinitrate infusion, 44 and injection of botulinum toxin to lower the pancreatic sphincter pressure 45 may augment pancreatic drainage. However these adjuvant interventions also present potential for complications, and their time or cost-effectiveness remains questionable.…”
Section: Complications 1) Post-epbd Pancreatitismentioning
confidence: 99%